2021
DOI: 10.1093/ckj/sfab002
|View full text |Cite
|
Sign up to set email alerts
|

Serum phosphorus and calcium levels, and kidney disease progression in immunoglobulin A nephropathy

Abstract: Background and objectives Disorders of calcium and phosphorus metabolism have been reported to be associated with all-cause and cardiovascular mortality in patients requiring long-term dialysis therapy. However, its role in disease progression is not well established in patients without dialysis, especially in IgA nephropathy. We aim to evaluate the association of serum phosphorus and calcium and progression of IgA nephropathy. Design, setting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 35 publications
1
4
1
Order By: Relevance
“…In a Chinese cohort of 957 IgAN patients with a median follow-up of 83 months, univariate Cox regression indicated that higher serum phosphorus levels were associated with disease progression, whereas the risk was attenuated after adjusting for other risk factors [18]. In contrast, our results showed higher levels of serum phosphorus were associated with greater risk of progression after adjustment for potential confounders including age, gender, eGFR, proteinuria, MAP, hemoglobin, Oxford S and T score, which was consistent with another large Chinese cohort study including 2,567 IgAN patients with a median follow-up of 31.90 months [19].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In a Chinese cohort of 957 IgAN patients with a median follow-up of 83 months, univariate Cox regression indicated that higher serum phosphorus levels were associated with disease progression, whereas the risk was attenuated after adjusting for other risk factors [18]. In contrast, our results showed higher levels of serum phosphorus were associated with greater risk of progression after adjustment for potential confounders including age, gender, eGFR, proteinuria, MAP, hemoglobin, Oxford S and T score, which was consistent with another large Chinese cohort study including 2,567 IgAN patients with a median follow-up of 31.90 months [19].…”
Section: Discussionsupporting
confidence: 89%
“…In a Chinese cohort of 957 IgAN patients with a median follow-up of 83 months, univariate Cox regression indicated that higher serum phosphorus levels were associated with disease progression, whereas the risk was attenuated after adjusting for other risk factors [18]. In contrast, our results showed higher levels of serum [19].…”
Section: Discussioncontrasting
confidence: 61%
“…With renal disorder development, elevated phosphorus concentrations may cause low circulating calcium concentration by accumulating onto the osseous matter and other tissues. Disturbances in the metabolic pathway of calcium metabolism disorders are characteristic features of chronic kidney disease (40) . In various investigations, the circulating concentration of phosphorus was confirmed as a principal health risk for heart failure and all-cause death in kidney failure patients.…”
Section: Figure 6 Serum Level Of Total Calciummentioning
confidence: 99%
“…IgA nephropathy is one of the most common primary glomerular diseases worldwide, and the leading cause of kidney failure requiring kidney replacement therapy [ 1–3 ]. The clinical presentation of in IgAN ranges from a benign incidental condition to progressive kidney failure.…”
Section: Introductionmentioning
confidence: 99%
“…The progression of IgA nephropathy is monitored by the presence of proteinuria, hypertension, changes in glomerular filtration rate (GFR), and Oxford classification MEST-C score [ 4–8 ]. In addition, persistent hematuria and hyperphosphatemia are associated with kidney disease progression in patients with IgA nephropathy [ 1 , 9–11 ].…”
Section: Introductionmentioning
confidence: 99%